Overview Dental Caries Knowledge Among Adolescents Aged 12-14 Years Using The Mystery Box Media at Hos Education Tutoring Center Surabaya 2025 - Hapsari, Mutiara Putri; Sugito, Bambang Hadi; Hadi, Sunomo (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Oral health is a crucial aspect of human life. Dental and oral health problems can affect overall physical health. However, public awareness of oral health still shows a less than optimal trend. The most common oral health problem is tooth decay, or dental caries. The WHO also designated the age of 12 to 15 as a milestone in the “Global Goals for Oral Hearth 2020”, which can be used to monitor dental disease. This study aims to identify information related to dental caries using mystery boxes in adolescents aged 12-14 at the Hos Education Surabaya tutoring center. This study employed a descriptive research design, and data collection was done using questionnaires distributed to 22 adolescents. Data analysis was performed by calculating the answer of each respondent and thaen converting them into percentages to determine the knowledge assessment category. The research results showed that the average knowledge of adolescents aged 12-14 years at the Hos Education tutoring center Surabaya using the mystery box media was 83%, categorized as good.